KELAHIRAN JAKA TARUB VERSISEH MAULANA MAGHRIBI: ANALISIS RESEPSI (The Birth Jaka Tarub in Seh Maulana Maghribi's Version: Reception Analysis) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This study is intended (1) to know the author's reception toward the legend of Jaka Tarub's birth in Babad Tanah Jawi (BTJ)